Adhesive behavior and pavement performance of asphalt mixtures incorporating red mud as a filler substitute. (6th September 2021) - Zhang, Jizhe; Li, Peizhao; Wang, Kai; Ma, Chuanyi; Liang, Ming; Jiang, Hongguang; Yao, Kai; Su, Chunhua; Yao, Zhanyong
Highlights: Adhesive behavior between red mud and bitumen can be improved by adding hydrated lime or Portland cement. Red mud improved the stiffness and elastic recovery of asphalt mastics which in turn enhanced the dynamic modulus of asphalt mixture. Hydrated lime and Portland cement can both improve the moisture resistance of red mud asphalt mixtures. Abstract: With the massive exploitation and utilization of no-renewable natural resources, good-quality road building materials has been becoming scare and it is an urgent demand to explore and develop alternatives. This study investigated feasible approaches of using red mud as a filler substitute to replace limestone powder in asphalt mixtures. In order to elaborate its influence on adhesive behavior, surface energy components of various fillers, base bitumen, the powder-bitumen interface and the aggregate-asphalt mastic interfaces were calculated and characterized. The mechanical properties of asphalt mastics and asphalt mixtures were assessed by using Quality Control Test (QCT), Hamburg Wheel Tracking (HWT) test and Simple Performance Test (SPT). Referring to the thermodynamic theory, the adhesive performance of the red mud-bitumen interface can be improved by the addition of hydrated lime or Portland cement and the moisture resistance of the aggregate-asphalt mastic bond can be enhanced. It was found that incorporating the red mud can improve the stiffness and the elastic recovery of asphalt mastic, which in turn had a potential to improve the high-temperature performance of the corresponding asphalt mixtures. Regarding to pavement performance, replacing limestone powder by red mud improved the rutting resistance of asphalt mixtures and the moisture resistance can be enhanced by incorporating a certain amount of hydrated lime or Portland cement.